Pigmentmodifikation und neuer Fundort von Aphelinus semiflavus How. (Hymenoptera: Chalcidoidea). - Janssen, Margot (Contributions to Entomology = Beiträge zur Entomologie, 1961)
In species of Chalcidoidea variability concerning pigmental and morphological characteristics should be observed more intensively. Aphelinus semiflavus Howard is a newly discovered example of pigmental variability. Its first discription made by Howard is completed. The chalcid, parasite of Myzodes persicae Sulz. was found for the first time in Germany in a green-house.